CD73 as a potential opportunity for cancer immunotherapy. (1st February 2019) - Ghalamfarsa, Ghasem; Kazemi, Mohammad Hossein; Raoofi Mohseni, Sahar; Masjedi, Ali; Hojjat-Farsangi, Mohammad; Azizi, Gholamreza; Yousefi, Mehdi; Jadidi-Niaragh, Farhad
ABSTRACT: Introduction : Cancer cells apply various mechanisms to induce and enhance immune escape. The complex network of immune-response modulating factors in the tumor microenvironment is a reason for the difficulties encountered when attempting to treat many cancers. Adenosine is a potent immune-modulating factor that can be generated through the degradation of ATP by cooperative action of NTPDase1 (CD39) and ecto-5ʹ-nucleotidase (CD73) molecules. Overexpression of CD73 on tumor and immune cells leads to the presence of a high concentration of this factor in the tumor region. Upregulation of CD73 is associated with the overproduction of adenosine; it suppresses antitumor immune responses and helps proliferation, angiogenesis, and metastasis. Areas covered : We attempt to clarify the immunobiology of CD73 in association with its role in cancer development, angiogenesis, and metastasis. Moreover, we have reviewed CD73-targeting studies and highlighted CD73 as a potent target for cancer immunotherapy. Expert opinion : It seems that blockade of CD73, in combination with immune checkpoint inhibitors such as anti-PD-L1 and anti-CTLA-4, can be a novel promising therapeutic strategy that can be evaluated in the future trials.